PENGARUH MODEL PEMBELAJARAN TGT BERBANTUAN “QUIZIZZ PAPER MODE” TERHADAP MINAT DAN HASIL BELAJAR KELAS V SDN PETOMPON 02 KOTA SEMARANG - Dhakar, Ronggo Alam; Andaryani, Eka Titi (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2024)
This study investigates the influence of the Teams Games Tournament (TGT) learning model with Quizizz Paper Mode on the interests and learning outcomes of Class V Mathematics. This type of research is Quasi Experimental with the Nonequivalent Control Group research design. The sample of the research was 27 pupils in 5a and 28 pupils of 5c from SDN Petompon 02 Kota Semarang. Both classes had the same abilities before being treated. After being treated, the experimental class had an average difference in interests and learning outcomes compared to the control class. This was demonstrated by the difference test obtained a value of significance <0,05. The results of the test of the hypothesis of influence of interest and learning results obtaining a significance value <0.05. So it can be concluded that the TGT learning model with Quizizz Paper Mode has an influence on learning Mathematics in elementary school.